Peran Filsafat Ilmu Dalam Pembelajaran Abad 21 - Erni Wantini Widaningsih; Weti Sri Nuryani Jamilah; Wina Pujilestari (Pusat Riset dan Inovasi Nasional, 2024)
In general, philosophy helps to understand things. Likewise, philosophy plays a role in learning in the 21st century. The research method used is qualitative research. Data is in the form of descriptions of words or phrases that describe the condition of the sample. Based on the research results, it was found that the philosophy of science plays a role as a basis for the development of science or theory. Philosophy of science also acts as a means of testing scientific theoretical reasoning. Philosophy of science is able to test, reflect, criticize assumptions and scientific methods in scientific research.